A New 2-way Multi-level Partitioning Algorithm. Issue 3 (2000) - Saab, Youssef
Abstract : Partitioning is a fundamental problem in the design of VLSI circuits. In recent years, the multi-level partitioning approach has been used with success by a number of researchers. This paper describes a new multi-level partitioning algorithm (PART) that combines a blend of iterative improvement and clustering, biasing of node gains, and local uphill climbs. PART is competitive with recent state-of-the-art partitioning algorithms. PART was able to find new lower cuts for many benchmark circuits. Under suitably mild assumptions, PART also runs in linear time.